2014
DOI: 10.1017/s1368980014002997
|View full text |Cite
|
Sign up to set email alerts
|

The impact of front-of-pack nutrition labels on consumer product evaluation and choice: an experimental study

Abstract: Objective: The present research was an experimental test that aimed to quantify the impact of two dominant front-of-pack (FOP) nutritional label formats on consumer evaluations of food products that carried them. The two FOP label types tested were the traffic light label and the Percentage Daily Intake. Design: A 4 × 5 partially replicated Latin square design was used that allowed the impact of the FOP labels to be isolated from the effects of the product and the consumers who were performing the evaluations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 17 publications
4
59
0
1
Order By: Relevance
“…While many studies have examined consumer comprehension and preference regarding front-of-pack nutrition labels [eg 1, 2, 3, 5], few studies have examined the impact on behaviour. One study conducted on university students in New Zealand [14] found that each of the front-of-pack labels tested led to significantly positive changes in purchase intention regardless of label type, size, or the nutritional quality of the food product carrying the label. A later study conducted in New Zealand on consumers recruited on exit from supermarkets by the same investigators [15] found that a HSR label decreased intention to purchase regardless of whether the product carried 5 stars or 2 stars.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined consumer comprehension and preference regarding front-of-pack nutrition labels [eg 1, 2, 3, 5], few studies have examined the impact on behaviour. One study conducted on university students in New Zealand [14] found that each of the front-of-pack labels tested led to significantly positive changes in purchase intention regardless of label type, size, or the nutritional quality of the food product carrying the label. A later study conducted in New Zealand on consumers recruited on exit from supermarkets by the same investigators [15] found that a HSR label decreased intention to purchase regardless of whether the product carried 5 stars or 2 stars.…”
Section: Discussionmentioning
confidence: 99%
“…The DIG is 43 known as a reductive FoPL because it does not provide an assessment of a product's 44 nutritional quality (Hamlin, McNeill, & Moore, 2014;Newman, Howlett, & Burton, 2014). 45 Evaluative FoPLs, on the other hand, provide an interpretation of the levels of nutrients 46 within a product (e.g., through colour and text).…”
mentioning
confidence: 99%
“…This research contributes to the discourse on policy-related influences on food choice with respect to government regulated labelling (e.g., Feunekes et al 2008;Hamlin et al, 2015;Pettigrew et al 2017;van Herpen & van Trijp, 2011), plus it addresses an important research gap by intersecting this line of research with previous works on product-related predictors and parents' individual decision-making (Symmank et al, 2017). Taken M A N U S C R I P T …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 90%
“…numerical information on key nutrients) and reductive (i.e. a summary assessment of the food's health value) elements (Hamlin, McNeill, & Moore, 2015) in the form of a visual star rating (from ½ to five stars) and summary nutrient facts panel. This panel information contains the amount of four 'risk' nutrients (energy, sugar, saturated fat and sodium) and one positive nutrient (e.g., dietary fiber or protein per 100g) (Department of Health, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%